DISCOVERY OF POTENT, ORALLY ACTIVE COMPOUNDS OF TYROSINE KINASE AND SERINE/THREONINE-PROTEIN KINASE INHIBITOR WITH ANTI-TUMOR ACTIVITY IN PRECLINICAL ASSAYS - Qiu, Yun-Qing; Zhou, Jue; Kang, Xin-Shan; Shen-Tu, Jian-Zhong; Ding, Lie-Ming; Tan, Fen-Lai; Guo, Jing; Li, Lan-Juan (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Traditional medicines have become the most productive source of leads for drugs development, particularly as anti-cancer agents. Various screening approaches are being applied. Sorafenib, a multikinase inhibitor, is used to treat primary kidney cancer (advanced renal cell carcinoma) and advanced primary liver cancer. A small library of compounds analogous to sorafenib were designed and screened for the treatment of liver cancer. Multiple members of the family in an assay panel of tyrosine kinase family and serine/threonine-protein kinase family, including VEGFR, Abl, Aurora A, p 38, Lck, Src, PDGFR, Flt3, c-RAF, c-KIT, MEK(MAPKK) were selected to test these compounds. Analysis of the selectivity patterns for these compounds shows specificity for many kinase families. IC50 were measured for the selected compounds. Multiple compounds have very similar kinase inhibition profiles of VEGFR, Flt3, FGFR to that of sorafenib. The IC50 of c-RAF of BB1 is lower than sorafenib. The IC50 of c-RAF of BB3-12 is higher than that of sorafenib. For Flt3, IC50 of BB1-4 is less than sorafenib. The IC50 value of KDR of BB1-10 is less than sorafenib. especially against c-RAF, PDGFR, c-KIT, KDR compared to sorafenib. These compounds are potent Raf1 and Flt4 kinase inhibitors.